Influence of alkyl chains on photovoltaic properties of 3D rylene propeller electron acceptors. Issue 7 (26th January 2017) - Fu, Huiting; Meng, Dong; Meng, Xiangyi; Sun, Xiaobo; Huo, Lijun; Fan, Yuzun; Li, Yan; Ma, Wei; Sun, Yanming; Wang, Zhaohui
Abstract : We demonstrate that fine-tuning alkyl substituents can effectively enhance photovoltaic properties of 3D rylene propeller-based non-fullerene electron acceptors. Abstract : A series of propeller-shaped triperylene hexaimide (TPH) non-fullerene acceptors, featuring branched alkyl side chains with different lengths (TPH-4, TPH-5, TPH-6, and TPH-7), have been designed and synthesized. The effects of the branched alkyl chain length on the physical properties, thin-film microstructure, molecular packing, charge transport and the resulting photovoltaic properties of these materials have been systematically investigated. It was found that TPH-7 with the longest alkyl side chain showed the best photovoltaic performance compared with three other TPH molecules, and an outstanding power conversion efficiency (PCE) of 8.6% under AM 1.5G irradiation (100 mW cm −2 ) has been obtained using a wide-band-gap polymer PDBT-T1 as the electron donor. These results demonstrate that finely tailoring alkyl substituents on TPH-based small molecular acceptors critically impacts the structural order of thin films and molecular orientation, and thus the photovoltaic performance.